2019
DOI: 10.1002/evan.21788
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and the evolution of Homo sapiens in Africa

Abstract: It has been proposed that a multiregional model could describe how Homo sapiens evolved in Africa beginning 300,000 years ago. Multiregionalism would require enduring morphological or behavioral differences among African regions and morphological or behavioral continuity within each. African fossils, archeology, and genetics do not comply with either requirement and are unlikely to, because climatic change periodically disrupted continuity and reshuffled populations. As an alternative to multiregionalism, I su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 90 publications
(96 reference statements)
0
25
0
1
Order By: Relevance
“…For post-50 ka populations, we argue that what is represented in the Eurasian archaeological record is probably the product of mixed populations (to a larger or lesser extent), instead of belonging solely to either the Neanderthals or to H. sapiens. Klein (2019) suggests that novel gene constellations post-50 ka gave rise to 'fully modern' people and the Later Stone Age in Africa. The fact that the precuneus in its current form is, however, already visible in the palaeoneurological record from1 00 ka during the MSA, reveals a different scenario.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For post-50 ka populations, we argue that what is represented in the Eurasian archaeological record is probably the product of mixed populations (to a larger or lesser extent), instead of belonging solely to either the Neanderthals or to H. sapiens. Klein (2019) suggests that novel gene constellations post-50 ka gave rise to 'fully modern' people and the Later Stone Age in Africa. The fact that the precuneus in its current form is, however, already visible in the palaeoneurological record from1 00 ka during the MSA, reveals a different scenario.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Some have suggested that this latter development occurred with a single sudden mutation or novel gene constellations at post-50 ka (e.g. Klein 2000Klein , 2019. It is our take, however, that human cognitive evolution is a long, incremental, multi-faceted, and continuous process.…”
Section: Introductionmentioning
confidence: 91%
“…The MSA/LSA transition was integrated into broader discussions of the evolution of H. sapiens only in the 1970s and achieved prominence in the late 1980s–1990s under the Human Revolution model, which, through the important and influential work of Klein and others, posited a single origin point for “modern” human behavior that arose as a genetic mutation somewhere in Africa, coincident with the appearance of LSA sites. Under this model and later variants of it, the mutation rapidly spread across and out of Africa ~40–50 ka through population contact or dispersal . Indeed, Klein's work in particular has been central to drawing attention to the MSA/LSA transition.…”
Section: What Are the Interesting Questions About The Msa/lsa Transitmentioning
confidence: 99%
“…Addressing any of these questions can proceed only with a well‐defined archeological record and a detailed understanding of the timing, tempo, and nature of the transition. While hypotheses related to genetic changes are important, they are not easily addressed with archaeological data, and are not my focus here.…”
Section: What Are the Interesting Questions About The Msa/lsa Transitmentioning
confidence: 99%
See 1 more Smart Citation